Serum sE-selectin Levels in Newly Diagnosed Psoriasis Patients and Correlation with Psoriasis Area and Severity Index Score - Shveta; Kiran Agarwal; Ranchander; Shilpi Agarwal (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Psoriasis is a chronic skin disorder with unknown aetiology affecting 125 million people worldwide. It is an inflammatory T-cell mediated disease. Few studies have reported increased expression of numerous adhesion molecules (ICAM-1, ICAM-3, sE-selectin) in the psoriatic skin. But whether they can be used as a marker of severity of the disease and immunotherapy targets is still questionable. Aim: To study the levels of sE-selectin in patients with psoriasis and correlate the sE-selectin level with disease severity. Secondly, to see the effect of six months of topical therapy i.e coal tar, salicylic acid and dithranol on sE-selectin levels. Materials and Methods: A descriptive cross-sectional hospital based study was conducted in the Department of Pathology in collaboration with the Department of Dermatology, Lady Hardinge Medical College and Associated Hospitals, New Delhi, India. A total of 52 newly diagnosed cases of psoriasis, attending the Dermatology OPD of Smt Sucheta Kriplani Hospital were included in the study group and severity score was calculated. Venous blood sample was taken from 52 patients and 30 age and sex matched controls comprising of healthy, non psoriatic volunteers with no family history of psoriasis. Blood sample was analysed for sE-selectin levels by ELISA (DIACLONE, France). Cases were followed at six months interval to study changes in sE-selectin levels after topical therapy. Statistical analysis was done using SPSS version 19.0. Paired t-test, ANOVA and pearson’s correlation coefficient was used for statistical analysis. Results: The levels of sE-selectin were significantly raised in the cases as compared to controls, correlated with disease severity and showed a reduction in the patients in which follow up was available. After six months of coal tar, salicylic acid and dithranol treatment, there was decrease in mean Psoriasis Area and Severity Index (PASI) and serum sE-selectin but not enough to reach a statistical significance. Conclusion: The sE-selectin levels are raised in patients of psoriasis and show reduction following therapy. They may be attractive targets for newer therapies in the future.